Anion-Exchange Membranes’ Characteristics and Catalysts for Alkaline Anion-Exchange Membrane Fuel Cells - Fa-Cheng Su; Hsuan-Hung Yu; Hsiharng Yang (Membranes)
This work aims at the effects of anion-exchange membranes (AEMs) and ionomer binders on the catalyst electrodes for anion-exchange membrane fuel cells (AEMFCs). In the experiments, four metal catalysts (nano-grade Pt, PtRu, PdNi and Ag), four AEMs (aQAPS-S8, AT-1, X37-50T and X37-50RT) and two alkaline ionomers (aQAPS-S14 and XB-7) were used. They were verified through several technical parameters examination and cell performance comparison for the optimal selection of AMEs. The bimetallic PdNi nanoparticles (PdNi/C) loaded with Vulcan XC-72R carbon black were used as anode electrodes by using the wet impregnation method, and Ag nanoparticles (Ag/C) were used as the catalyst cathode. It was found that the power density and current density of the X37-50RT are higher than the other three membranes. Also, alkaline ionomers of XB-7 had better performance than aQAPS-S14. The efficiency was improved by 32%, 155% and 27%, respectively, when compared to other membranes by using the same catalyst of PdNi/C, Ag/C and Pt/C. The results are consistent with the membrane ion conductivity measurements, which showed that the conductivity of the X37-50RT membrane is the highest among them. The conductivity values for hydroxide ions (OH−) and bromide ions (Br−) are 131 mS/cm and 91 mS/cm, respectively. These findings suggest that the properties (water uptake, swelling rate and mechanical) of the anion-exchange membrane (AEM) can serve as a key reference for AEM fuel cell applications.